Please use "^" to denote exponentiation: f(x) = x^2 - 6x.
To find f(-a), replace "x" with "(-a)" in the function (x) = x^2 - 6x:
f(-a) = (-a)^2 - 6(-a) = a^2 + 6a (answer)
Answer:
hey sorry nobody now the answer but i really need the points
Step-by-step explanation:
Answer:
i dont now..............................
Step-by-step explanation:
Answer:
The age of each person is:
- Jess is <u>21</u> years old.
- Mac is <u>66</u> years old.
Step-by-step explanation:
To solve this problem you must make two equations. First, we name Jess and Mac as variables:
j = Jess age.
m = Mac age.
Now we make the equations, the first equation has the information "Jess is 12 years less than half as old as Mac":
1. ![j=(\frac{m}{2})-12](https://tex.z-dn.net/?f=j%3D%28%5Cfrac%7Bm%7D%7B2%7D%29-12)
The second equation has the information "The sum of their age is 87":
2. ![j+m=87](https://tex.z-dn.net/?f=j%2Bm%3D87)
Now, we replace the first equation in the second one:
And we operate:
We clear the variable m:
How we know Mac's age is 66 years old, we can identify Jess' age with the second equation:
We replace the value of m:
And clear the variable j:
In the end, Jess's age is 21 years old.
Answer:
29
Step-by-step explanation:
x+11÷8=5
5 × 8 = 40
40- 11 = 29
29 + 11 ÷ 8 =5